2023
DOI: 10.1177/03635465231175476
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Missed Statin Therapy and 10-Year Atherosclerotic Cardiovascular Disease Risk Score to Retear Rate After Arthroscopic Rotator Cuff Repair

Abstract: Background: There is no practical consensus on managing cholesterol in patients with rotator cuff repair despite hyperlipidemia and statin therapy being well-known factors in rotator cuff healing. The 10-year atherosclerotic cardiovascular disease (ASCVD) risk score is a commonly used guideline to determine statin administration for hyperlipidemia. Purpose: To identify the relationship between retear and preoperative factors, including 10-year ASCVD risk score and statin administration status, and to compare c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A clinical study by Cancienne et al ( 25 ) revealed a positive correlation between perioperative lipid levels and the rate of revision surgery following rotator cuff repair, suggesting that statin therapy could potentially decrease this revision rate. Similarly, a recent case–control study by Lee et al ( 50 ) incorporated 104 hyperlipidemic patients who underwent arthroscopic rotator cuff repair, among whom 66 individuals were in the statin group and 38 in the non-statin group. The follow-up findings indicated a lower re-tear rate in the statin group.…”
Section: Application Of Lipid-lowering Drugs In Rotator Cuff Injuries...mentioning
confidence: 99%
“…A clinical study by Cancienne et al ( 25 ) revealed a positive correlation between perioperative lipid levels and the rate of revision surgery following rotator cuff repair, suggesting that statin therapy could potentially decrease this revision rate. Similarly, a recent case–control study by Lee et al ( 50 ) incorporated 104 hyperlipidemic patients who underwent arthroscopic rotator cuff repair, among whom 66 individuals were in the statin group and 38 in the non-statin group. The follow-up findings indicated a lower re-tear rate in the statin group.…”
Section: Application Of Lipid-lowering Drugs In Rotator Cuff Injuries...mentioning
confidence: 99%